2016
DOI: 10.1007/s12328-016-0670-7
|View full text |Cite
|
Sign up to set email alerts
|

Current status and future prospects of chemotherapy for advanced hepatocellular carcinoma

Abstract: Sorafenib is the only drug that demonstrates a survival benefit for advanced hepatocellular carcinoma (HCC). However, the therapeutic effect of sorafenib is limited, so development of a more effective treatment method and second-line treatments is needed. Since the advent of sorafenib, clinical studies have been conducted with a variety of drugs and treatment methods, mainly with molecular targeted therapy, but almost all trials have ended in failure. The reasons for the difficulty in the development of a nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…Several prospective trials have shown unequivocal clinical activity in melanoma and NSCLC (reviewed in [77]). Many trials are focusing on molecular targeted agents in HCC, but most have ended in failure except sorafenib [102, 103] and even this agent shows only a limited increase in survival of approximately 3 months for advanced HCC [104]. Disappointingly, however, BM is a contraindication for sorafenib [105].…”
Section: Radiotherapymentioning
confidence: 99%
“…Several prospective trials have shown unequivocal clinical activity in melanoma and NSCLC (reviewed in [77]). Many trials are focusing on molecular targeted agents in HCC, but most have ended in failure except sorafenib [102, 103] and even this agent shows only a limited increase in survival of approximately 3 months for advanced HCC [104]. Disappointingly, however, BM is a contraindication for sorafenib [105].…”
Section: Radiotherapymentioning
confidence: 99%
“…Sorafenib, a serine-threonine kinase inhibitor, is currently the only approved systematic drug for anti-HCC. Unfortunately, the efficacy of sorafenib is limited, and some patients are intolerant [3]. Therefore, more effective therapeutic strategies for HCC are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, they do not effectively control distant metastasis rates. Thus, there is unanimous agreement for the urgent requirement to develop novel, more effective drugs and treatment methods for the clinical treatment of HCC (5,15). One suggested approach is to identify drugs that are derived from natural compounds with anticancer activity.…”
Section: Introductionmentioning
confidence: 99%